Mutations in HSPB8 causing a new phenotype of distal myopathy and motor neuropathy. (26th January 2016) - Ghaoui, Roula; Palmio, Johanna; Brewer, Janice; Lek, Monkol; Needham, Merrilee; Evilä, Anni; Hackman, Peter; Jonson, Per-Harald; Penttilä, Sini; Vihola, Anna; Huovinen, Sanna; Lindfors, Mikaela; et al.
Abstract : Objective: To report novel disease and pathology due to HSPB8 mutations in 2 families with autosomal dominant distal neuromuscular disease showing both myofibrillar and rimmed vacuolar myopathy together with neurogenic changes. Methods: We performed whole-exome sequencing (WES) in tandem with linkage analysis and candidate gene approach as well as targeted next-generation sequencing (tNGS) to identify causative mutations in 2 families with dominant rimmed vacuolar myopathy and a motor neuropathy. Pathogenic variants and familial segregation were confirmed using Sanger sequencing. Results: WES and tNGS identified a heterozygous change in HSPB8 in both families: c.421A > G p.K141E in family 1 and c.151insC p.P173SfsX43 in family 2. Affected patients had a distal myopathy that showed myofibrillar aggregates and rimmed vacuoles combined with a clear neurogenic component both on biopsy and neurophysiologic studies. MRI of lower limb muscles demonstrated diffuse tissue changes early in the disease stage progressing later to fatty replacement typical of a myopathy. Conclusion: We expand the understanding of disease mechanisms, tissue involvement, and phenotypic outcome of HSPB8 mutations. HSPB8 is part of the chaperone-assisted selective autophagy (CASA) complex previously only associated with Charcot-Marie-Tooth type 2L (OMIM 60673) and distal hereditary motor neuronopathy type IIa. However, we now demonstrate that patients can develop a myopathy with histologic features of myofibrillar myopathy with aggregates and rimmed vacuoles, similar to the pathology in myopathies due to gene defects in other compounds of the CASA complex such as BAG3 and DNAJB6 after developing the early neurogenic effects.